Disciplinary Differences for Undergraduate ESL Writers in University Courses in the United States - K. James Hartshorn; Norman W. Evans; Jesse Egbert; Amy Johnson (Journal of Linguistics and Language Teaching)
Building on previous research, this study explored differences in university professors’ perceptions about writing from the beginning to the end of the baccalaureate experience across five common disciplines including biology, business, computer science, engineering, and psychology. Survey data provide insights regarding the relative importance of various aspects of writing along with information about the volume of writing, the extent to which feedback was provided and resubmissions were allowed, the types of writing completed for exams, the greatest writing challenges, and the most salient writing purposes across disciplines and over time. While factors such as the writing challenges students faced, seemed unaffected by discipline or time in a particular discipline, other factors were noticeably influenced by the students’ specific discipline, whether students were at the beginning or end of their baccalaureate experience, or both. These factors included distinct differences in the purposes of writing as well as different perceptions of the importance of various aspects of writing across disciplines. An understanding of both these commonalities as well as the differences should be useful for practitioners and university administrators as well as the students themselves.